(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: Describe the current situation and analyze some factors related to anxiety disorder among healthcare workers during the COVID-19 pandemic and some related factors. Subjects and Methods: We conducted a cross-sectional descriptive study involving 922 Saint Paul Hospital staff members who willingly participated in the research. Anxiety disorder levels were assessed using the GAD-7 scale. We examined relevant factors such as demographic characteristics and the work environment of healthcare workers during the pandemic. Results: The study found that the prevalence of anxiety disorder among medical staff at Saint Paul General Hospital was 38.8%. Several factors were identified as significantly associated with higher rates of anxiety disorder, including being male, single, having less than 10 years of service, working more than 5 days per week, and working more than 8 hours per day. Conclusion: The research revealed a relatively high prevalence of anxiety disorder (38.8%) among healthcare workers at Saint Paul Hospital during the COVID-19 pandemic. Additionally, the study highlighted that longer working hours, gender, and singer status were significant contributing factors to the increased occurrence of anxiety disorder among healthcare workers.